ANALISIS KEPUASAN PESERTA DIDIK BERDASARKAN KUALITAS PELAYANAN DI SMK BATIK 1 SURAKARTA - Wahyu Yudha Pranoto; Sunarto Sunarto; Salman Alfarisy Totalia (Department of Economics Education, Universitas Sebelas Maret, 2018)
The purpose of this study was to determinethe suitability level of service quality performanceat SMK Batik 1which includes tangible, reliability, responsiveness, assurance, and empathy simultaneously and partially.This study uses survey research methods. The study population was SMK Batik 1 Surakarta. Samples were taken by proportional random technique. The research data obtained by questionnaire. The validity of the data carried by the internal validity. Analysis of the data used in this research is the analysis of Importance Performance Analysis (IPA).The conclusion of this study were: 1) the satisfaction of students is lower than the quality of service in SMK Batik 1 Surakarta. 2) The high level of expectation of students on the performance of services seen from the dimensions of service quality has been determined, indicating that the level of expectation of students on a quality service at SMK Batik 1 Surakarta is quite important. 3) The low level of performance of service quality as seen from the dimensions of service quality has been determined show that the level of quality of service performance in SMK Batik 1 Surakarta is unsatisfactory students. 4) 30 indicators that are analized then there are 6 indicators included in the quadrant A, which is the main priority, 10 indicators are included in quadrantgB (performance and expevtation was based), who fall into quadrant C there are 7 indicators (low priority), 7 indicators included in quadrant D (be overestimated by students)